Hajj: Between Thirst of Spirituality, Symbolic Capital and Fetishism in the Sasak’s Lombok - Abdul Rahim (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2022)
Nowadays hajj become a social class in Sasak society, with the symbolic capital attached to it making the title holder also try to construct a strategy about distinguishing itself (distinction) through costumes, daily attitudes, and what they consumed. This paper explores the correlation between the hajj title and the symbolic capital that they achieve for being a pilgrimage to Mecca, and how the role of hajj in Sasak people to strengthen ummah is compared to the common people that legitimate the new social class as different as them in the community. The genealogy of hajj titles that make up social class is studied through Pierre Bourdieu's concept of Social Praxis related to symbolic capital and distinction. This study used a new ethnography concept from Paula Saukko such as self-reflexivity, polivocality, and between self and others to explore the data. As a result, the hajj title becomes the identity as well as the legitimacy of the position of the Hajj subject in society. Even in some areas of Lombok, the title of hajj is an effort to move away from the low social class and can be equivalent to the social class of nobility. The critic of the study of hajj and umra cannot ignore the commercialisation of hajj or umra travel, which further emphasises the commodification of religion and also increasingly envelops the people in a pseudo-consciousness.